Women negotiating peace: A step toward durable peace? - Julika Holdmann; Dennis Lucy Avilés Irahola; Katharina Löhr (University of Bonn, Center for Development Research (ZEF), 2024)
This study investigates whether including women in peace negotiations has facilitated lasting peace. We argue that female negotiators and the action of women's civil society groups that advocate for gender-related provisions strengthen peace durability. We contend that genderspecific considerations during peace negotiations create conditions for more gender-equal societies that, in turn, makes peace more stable. This study applies a new approach in its analysis by linking women's participation in peace processes with gender-related provisions and peace durability. An analysis of a series of peace agreements signed from 1989 to 2018 through a Cox regression shows a significant decrease in the recurrence of conflict when at least one woman was a signatory of the agreement. Yet, due to the limited number of nine cases with female signatories, it is not possible to generalize the results. The regression analysis also reveals that gender-related provisions that do not address changes in gender relations do not affect peace durability significantly. As the Colombian and Mindanao (Philippines) cases demonstrate, women's participation in peace negotiations is no guarantee of lasting peace, thus highlighting the relevance of contextualized studies. The cases' analysis underscores the importance of addressing gender power dynamics thoroughly and implementing gender-inclusive provisions in peace agreements.
Keywords: 330; women; peace negotiations; gender-related provisions; conflict; peacebuilding